The Effect of Anodic Oxidation Voltages on the Color and Corrosion Resistance of Commercially Pure Titanium (CP-Ti): - - Kandice Felisha Kurniawan; Ika Maria Ulfah; Muhammad Kozin (PT. ELSHAD TECHNOLOGY INDONESIA, 2023)
The effect of anodic oxidation (or anodizing) voltages on the color and corrosion resistance of pure titanium was studied. In this experiment, a commercially-pure titanium was used. To create an